2013
DOI: 10.1007/s12600-013-0289-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects upon biological performance and lambda-cyhalothrin susceptibility in the multicolored Asian lady beetle, Harmonia axyridis

Abstract: Considered a generalist species among the coccinellids, the multicolored Asian lady beetle Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) feeds upon small arthropods and non-prey plant products, a practice which might enhance its ability to colonize various ecosystems but carries the potential to expose it to prey quality variation and insecticide use. Thus, we examined the effect of four different diets on the development, reproduction, and response to the insecticide lambda-cyhalothrin in this specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…; Dos Santos Rodrigues et al. ; Reznik and Vaghina ), In the present study, we first demonstrated the same difference between the suitability of these two diets for a closely related species, H. yedoensis .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…; Dos Santos Rodrigues et al. ; Reznik and Vaghina ), In the present study, we first demonstrated the same difference between the suitability of these two diets for a closely related species, H. yedoensis .…”
Section: Discussionsupporting
confidence: 75%
“…; Hodek and Evans ; Dos Santos Rodrigues et al. ; Reznik and Vaghina ), and thus, the weakening of the photoperiodic response automatically placed the females under the control of the trophic factor. This evolutionary trend is common among aphidophagous coccinellids because ‘unpredictable intermittent availability of aphid prey leads to a greater plasticity of diapause mechanisms’ (Hodek ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A rapid increase in foliar insecticide use occurred in Michigan in 2005 in response to a severe aphid outbreak in the state in that year (Fig. Foliar-applied pyrethroids are broad-spectrum and are associated with a negative impact on Harmonia populations when applied to soybean with high aphid populations (Ohnesorg et al 2009, dos Santos Rodrigues et al 2013. Two different insecticidemediated mechanisms could be involved in causing this phase shift: mortality of Harmonia as a direct result of pesticide spraying or indirect insecticide effects, due to the cascading effects of reduced availability of prey (cf.…”
Section: Previous Studies Have Commented On the Link Betweenmentioning
confidence: 99%